Changes in photosynthesis and chlorophyll fluorescence in two soybean (Glycine max) varieties under NaCl stress - Luo, Bin; Wang, Cheng; Wang, Xiaodong; Zhang, Han; Zhou, Yanan; Wang, Wensen; Song, Peng (International Journal of Agricultural and Biological Engineering, 2021)
Traditional detection methods of crop information are often destructive and low efficiency. In this study, a new evaluation method was developed based on photosynthesis and chlorophyll fluorescence. Via analysis of the changes under NaCl stress during the seedling stage of two varieties, the salt resistance mechanism of soybeans was explored and a non-destructive stress-recognition method was developed. In this experiment, two soybean varieties were treated with one of four levels of NaCl stress: CK (0 mmol/L), LS (50 mmol/L), MS (100 mmol/L), and HS (150 mmol/L), for 15 d. The normal functions of the photosynthetic system of soybeans were enhanced under LS NaCl stress, but were inhibited under HS NaCl stress. Biomass, net leaf photosynthetic rate (Pn), stomatal conductance (gs), intercellular carbon dioxide concentration (Ci), transpiration rate (Tr), chlorophyll fluorescence parameters Y(II) and PSII decreased. However, in contrast to the findings of other studies on the influence of severe drought stress on soybean for long periods in which non-photochemical quenching coefficient (qN) decreased, this parameter increased under salt stress in soybean. The results demonstrate that the method developed is a promising tool for rapid and non-destructive detection of soybean photosynthetic responses under salt stress in the field.Keywords: biomass, chlorophyll fluorescence parameters, NaCl stress, photosynthetic parameters, soybeanDOI: 10.25165/j.ijabe.20211403.5941Citation: Luo B, Wang C, Wang X D, Zhang H, Zhou Y N, Wang W S, et al. Changes in photosynthesis and chlorophyll fluorescence in two soybean (Glycine max) varieties under NaCl stress. Int J Agric & Biol Eng, 2021; 14(3): 76–82.